Investigation of ULF magnetic pulsations, air conductivity changes, and infra red signatures associated with the 30 October Alum Rock M5.4 earthquake - T. Bleier (Natural Hazards and Earth System Sciences, 2009)
Several electromagnetic signal types were observed prior to and immediately after 30 October 2007 (Local Time) M5.4 earthquake at Alum Rock, Ca with an epicenter ~15 km NE of San Jose Ca. The area where this event occurred had been monitored since November 2005 by a QuakeFinder magnetometer site, unit 609, 2 km from the epicenter. This instrument is one of 53 stations of the QuakeFinder (QF) California Magnetometer Network-CalMagNet. This station included an ultra low frequency (ULF) 3-axis induction magnetometer, a simple air conductivity sensor to measure relative airborne ion concentrations, and a geophone to identify the arrival of the P-wave from an earthquake. Similar in frequency content to the increased ULF activity reported two weeks prior to the Loma Prieta M7.0 quake in 1989 (Fraser-Smith, 1990, 1991), the QF station detected activity in the 0.01–12 Hz bands, but it consisted of an increasing number of short duration (1 to 30 s duration) pulsations. The pulsations peaked around 13 days prior to the event. The amplitudes of the pulses were strong, (3–20 nT), compared to the average ambient noise at the site, (10–250 pT), which included a component arising from the Bay Area Rapid Transit (BART) operations. The QF station also detected different pulse shapes, e.g. negative or positive only polarity, with some pulses including a combination of positive and negative. Typical pulse counts over the previous year ranged from 0–15 per day, while the count rose to 176 (east-west channel) on 17 October, 13 days prior to the quake. The air conductivity sensor saturated for over 14 h during the night and morning prior to the quake, which occurred at 20:29 LT. Anomalous IR signatures were also observed in the general area, within 50 km of the epicenter, during the 2 weeks prior to the quake. These three simultaneous EM phenomena were compared with data collected over a 1–2-year period at the site. The data was also compared against accounts of air ionization reported to be associated with radon emission from the ground (Ouzounov, 2007), and a series of laboratory rock stressing experiments (Freund, 2006, 2007a, b, c) to determine if field data was consistent either of these accounts. We could not find a data set with pre-earthquake radon measurements taken near the Alum Rock epicenter to compare against our field data. However, based on the Alum Rock data set example and another data set at Parkfield, the field tests are at least consistent with the lab experiments showing currents, magnetic field disturbances, air conductivity changes, and IR signatures. This is encouraging, but more instrumented earthquake examples are needed to prove a repeating pattern for these types of pre-earthquake EM signatures.